Evidence of the presence of minor tautomeric forms in selected nitroanilines. (11th December 2020) - Colasurdo, Diego D.; Pila, Matías N.; Laurella, Sergio L.; Allegretti, Patricia E.; Ruiz, Danila L.
Abstract : Rationale: Nitroanilines can exist in several tautomeric forms: nitro‐amino, nitro‐imino, and aci‐imino . The importance of evaluating minor tautomeric species comes from the fact that even less abundant tautomers have been proved to play important roles in reaction mechanisms. Methods: Electron ionization mass spectra of the pesticide Pendimethalin and four related nitroanilines were recorded at 70 eV to find information about the presence of minor tautomeric forms in the gas phase. The existence of the possible tautomers was evaluated by studying specific fragmentation pathways, which were confirmed by tandem mass spectrometry (MS/MS) experiments. Further supporting information was obtained by studying the structures of some intermediate compounds by theoretical calculations at the B3LYP 6‐311++G(d, p) level. Results: The mass spectrum of Pendimethalin suggests the coexistence of the nitro‐amine tautomer (the most stable form) with four possible less stable tautomers in equilibrium. The fragmentation routes were used to explain analogous peaks in two related compounds. However, the spectra of two other related compounds that cannot follow the proposed route of fragmentation for nitro‐imine tautomers do not show the analogous peak. Theoretical calculations were used to correlate the precursor cation with the proposed fragmentation pathway. Conclusions: By the study of mass spectra and proposed fragmentation pathways it can be concluded that, although the nitro‐amine is the most abundant species within the system, minor tautomers ( nitro‐imine and aci‐imine ) coexist in the gas phase.